2016
DOI: 10.4103/0973-1482.146130
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of microRNA-301a in nonsmall-cell lung cancer and its clinical significance

Abstract: miR-301a may represent a novel prognostic indicator, a biomarker for the early detection of lymph node metastasis and a therapeutic target in NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…An aberrant expression of miRNAs has been observed in the pathogenesis of several diseases, including various human cancers [28]. Shi et al indicated an overexpression of miR-301a in NSCLC tissues [29]. Furthermore, a research observed an upregulated miR-301b expression in lung cancer tissues and cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…An aberrant expression of miRNAs has been observed in the pathogenesis of several diseases, including various human cancers [28]. Shi et al indicated an overexpression of miR-301a in NSCLC tissues [29]. Furthermore, a research observed an upregulated miR-301b expression in lung cancer tissues and cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…Intronic miR-301a, which is one of two mature forms of miR-301 (miR-301a and miR-301b), and its host gene, SKA2 (spindle and kinetochore-associated protein 2), are located on chromosome 17q22–23 in the human genome 25 . MiR-301a has been reported to be dysregulated not only in breast cancer 22 , 23 , 26 but also in a variety of malignant tumours, including prostate, gastric, pancreatic, lung, blood, colourectal, and melanoma 17 19 , 21 , 25 , 27 29 . As most studies have concluded, miRNA-301a was identified as an oncogenic miR, which played an important role in activating tumour cell invasion/migration, promoting cell proliferation, inhibiting apoptosis and enhancing chemosensitivity both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, deletion of miR-301a in hematopoietic cells leads to reduced development of colitis-associated colon cancer [15]. In patients with NSCLC, miR-301a is most highly expressed in tumor tissues and is associated with poor differentiation and lymph node metastasis [16]. Collectively, these in vitro and in vivo data indicate that miR-301a has an important role in the tumor microenvironment and tumor metastasis.…”
Section: Introductionmentioning
confidence: 99%